DIASTOLIC DYSFUNCTION AS AN EARLY INDICATOR OF ANTHRACYCLINE-INDUCED CARDIOTOXICITY IN BREAST CANCER PATIENTS: A SYSTEMATIC REVIEW - Mainka, Tomasz; Sergejuk, Emil; Kotlarski, Wojciech; Kotlarska, Klaudia Magdalena (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Breast cancer is one of the most common malignancies worldwide, and anthracyclines remain a cornerstone of its treatment. However, their use is associated with the risk of cardiotoxicity, which may lead to subclinical myocardial injury, progressive ventricular dysfunction, and heart failure. Although left ventricular ejection fraction is still widely used in routine surveillance, it often decreases relatively late. Therefore, increasing attention has been directed toward diastolic dysfunction as a possible earlier marker of anthracycline-induced cardiac injury.Methods: A systematic review was conducted using the PubMed database. The search strategy included the terms “breast cancer” OR “breast neoplasms,” “anthracycline” OR “doxorubicin” OR “epirubicin,” and “diastolic dysfunction” OR “diastolic function.” The search was limited to studies published between 2010 and 2026, written in English, and conducted in humans. A total of 43 records were identified. After title and abstract screening, 15 full-text articles were assessed for eligibility. Fourteen studies met the inclusion criteria and were included in the final qualitative synthesis.Results: The reviewed studies showed that anthracycline therapy was associated with worsening of conventional and tissue Doppler indices of diastolic function, including E/A ratio, deceleration time, e′ velocity, and E/e′ ratio, often despite preserved left ventricular ejection fraction. Several studies also demonstrated abnormalities in more advanced echocardiographic markers, such as diastolic strain rate, diastolic strain time, left atrial strain, and intrinsic wave velocity propagation. In longitudinal analyses, early diastolic dysfunction was associated with later worsening of global longitudinal strain, decline in left ventricular ejection fraction, or subsequent cancer therapy-related cardiac dysfunction.Conclusions: Diastolic dysfunction appears to be a clinically relevant and potentially early marker of anthracycline-induced cardiotoxicity in breast cancer patients. Its earlier recognition may support closer cardio-oncology surveillance, improve risk stratification, and help identify patients who may benefit from earlier specialist evaluation and consideration of cardioprotective strategies before overt systolic dysfunction develops. Further prospective studies are needed to determine which diastolic parameters are the most sensitive and clinically useful in routine practice.